A Survey of Literary Citations to Kumeitâs Poems - Sayyed Heidar Shirazi (دراسات في اللغة العربيّة وآدابها)
This article discusses the literary character of Kumeit, a renowned Shiâite poet during Umayyad dynasty. It attempts to defend the credibility of the citations made to Kumeitâs Poems. It also responds to some of the misgivings about this credibility. To this end, major literary works have been examined in order to explain the different literary and poetic techniques and devices such as lexicon, grammar and syntax, rhetoric, and the related disciplines such as jurisprudence, interpretation and commentary of the holy Prophetâs sayings and parables have been explained. Moreover, this study gives an estimation of the number of the literary references made to Kumeit in these resources and some of them have been referred to as examples. Of course, it should be noted that despite heavy criticisms and accusations directed toward him both during his lifetime and after his death, Kumeit has been the focus of attention of great literary figures. His poems have frequently been cited in different areas such as lexicon.